A win–win team formation problem based on the negotiation. (September 2015) - Wang, Jian; Zhang, Jia
Abstract: Nowadays, many researches focus on the selection of the team members, and aim to form a team that can solve a common task collaboratively or achieve a certain goal cooperatively. The leader or manager needs to maximize the benefit of the team by selecting the appropriate team members from the available candidates. However, the personal opinions of team members have not been considered in the team formation process. In this paper, in order to consider the mutual decision between the leader and the team members, a negotiation based team formation problem is defined firstly, in which the balance of the benefit requirements of the leader and the team members is addressed. Then, a negotiation model between the leader and the team members is proposed to implement the team formation process. According to the conflicts in the process, an incentive mechanism based on the payoff is adopted. Finally, the agent-based negotiation approach is introduced to construct the simulation environment of the negotiation. The negotiation process is iterated until the benefit requirements of the leader agent and the candidate agents are all satisfied or the deadline of the negotiation is reached. The experiment results indicate that the team can be formed successfully in different team contexts, such as different team sizes, different minimum criteria of team positions and different incentive levels. Comparing with the leader׳s unilateral decision process, the negotiation-based team formation can make the team members acquire more benefits. In addition, the different preferences of the candidates have different effects on the final benefit acquirements, and the different minimum criteria of team positions and incentive levels have different effects on the conflicts resolution. Abstract : Highlights: The mutual-decision between leader and members is considered in the team formation. A negotiation model is proposed to implement the team formation process. A payoff based incentive mechanism is introduced to solve the benefit conflicts. An agent-based negotiation approach is used to address the team formation problem. The requirements of leader and members can be balanced through negotiation.